A Comprehensive 2D FE-SIBC Model for Calculating the Eddy Current Losses in a Transformer Tank-Wall - Díaz-Chacón, J. M.; Hernandez, C.; Arjona, M. A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The calculation of the eddy-current losses is one of the most important aspects that must be considered in the design of transformers and electrical machines. In this paper, a comprehensive 2D finite element (FE) model for calculating the eddy-current losses in a tank-wall of the transformer is presented. The FE model takes into account the Surface Impedance Boundary Condition (SIBC). A detailed 2D-SIBC formulation in terms of the magnetic vector potential is described. The SIBC is incorporated into the FE formulation by using the Galerkin method. An axi-symmetric electromagnetic model of the transformer is solved by applying the SIBC formulation for calculating the loss intensity distribution along the vertical tank-wall. To demonstrate the validity of the SIBC formulation, the results are compared against those computed with a model based on first-order triangular elements. The advantages of using the SIBC formulation in the modeling of power transformers are highlighted.